Retrospective Analysis of Serotype Switching of Vibrio cholerae O1 in a Cholera Endemic Region Shows It Is a Non-random Process. - Stefan L Karlsson; Nicholas Thomson; Ankur Mutreja; Thomas Connor; Dipika Sur; Mohammad Ali; John Clemens; Gordon Dougan; Jan Holmgren; Michael Lebens (PLoS Neglected Tropical Diseases)
Genomic data generated from clinical Vibrio cholerae O1 isolates collected over a five year period in an area of Kolkata, India with seasonal cholera outbreaks allowed a detailed genetic analysis of serotype switching that occurred from Ogawa to Inaba and back to Ogawa. The change from Ogawa to Inaba resulted from mutational disruption of the methyltransferase encoded by the wbeT gene. Re-emergence of the Ogawa serotype was found to result either from expansion of an already existing Ogawa clade or reversion of the mutation in an Inaba clade. Our data suggests that such transitions are not random events but rather driven by as yet unidentified selection mechanisms based on differences in the structure of the O1 antigen or in the serotype-determining wbeT gene.